Overexpression of the gene product of ocular albinism 1 (GPR143/OA1) but not its mutant forms inhibits neurite outgrowth in PC12 cells - Daiki Masukawa; Kaisei Yamada; Yoshio Goshima (Elsevier, 2019)
Neurite outgrowth is a complex differentiation process regulated by external and/or internal mechanisms. Among external mechanisms, G-protein coupled receptors (GPCRs) have been implicated in this process, but the pathways involved are not fully understood. L-3,4-dihydroxyphenylalanine (l-DOPA) is considered to be inert by itself, and to relieve Parkinson's disease through its conversion to dopamine. We have proposed that l-DOPA acts as a neurotransmitter. GPR143, the gene product of ocular albinism 1 (OA1), was identified as a receptor for l-DOPA. OA1 is an X-linked disorder characterized by all typical visual anomalies associated with hypopigmentation and optic misrouting, resulting in severe reduction of visual acuity. However, the molecular basis for this phenotype remains unknown. To study the function of GPR143, we investigated the phenotypic effect of overexpression of GPR143 in pheochromocytoma (PC12) cells treated with nerve growth factor. Overexpression of mouse GPR143 inhibited neurite outgrowth, and the effect was mitigated by l-DOPA cyclohexylester, an antagonist for l-DOPA. Furthermore, knockdown of G-protein Gα13 attenuated mouse GPR143 induced inhibition of neurite outgrowth. Human wild-type (wt) GPR143 also inhibited neurite outgrowth, but its mutants did not mimic the effect of wt GPR143. Our results provide a mechanism for axon guidance phenotype in ocular albinism 1. Keywords: GPR143, Neurite outgrowth, Pheochromocytoma cell, l-DOPA, Ocular albinism 1